Desarrollo de una aplicación para dispositivos móviles que oferte los servicios de reconstrucción, remodelación y rediseño de espacios interiores (2024)
This research aims to develop an application for mobile devices that allows users from strata 1, 2 and 3 in the city of Barranquilla Colombia access easily and simply at services such the reconstruction, remodeling and redesign of spaces, among others. To satisfy the current demand for this type of services that the market requires. It should be noted that, currently in the country, the development of specialized pages and mobile applications is required to generate a greater supply in response to the existing demand which, after the covid 19 pandemic, has become evident that it is a required service. that is not being provided, and the few applications existing do not provide this type of services and the few that have similar services offer them as complementary or additional services and not as main services. In this study, analytical-descriptive research is used, and the design to be worked in this research is explanatory because its interest is focused on explaining why a phenomenon occurs and under what conditions it occurs. The deductive analytical method will be used. It consists of the examination of a particular fact, which allows us to know more about the object of study, to better explain and understand its behavior and establish new theories. Carrying out the research allowed us to obtain the following results: Applications for mobile devices are one of the most unexplored market segments by construction companies in the city of Barranquilla, and therefore making proper and efficient use of them can lead to great business financial results. In strata 1, 2 and 3 of the city of Barranquilla the demand for construction services is high and therefore implementing an application that offers services in that area can help in attracting new potential and real clients. Consequently, recommendations were made such as: Implement the creation of applications for mobile devices in construction services, as a corporate strategy to access new markets, even those that are difficult to access regardless of condition. Applications for mobile devices that provide integrated construction services can have positive repercussions on the consumption indicators of each company, taking into account that it is a market with high growth potential.